If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5 = 3x + 19 Reorder the terms: -5 + 6x = 3x + 19 Reorder the terms: -5 + 6x = 19 + 3x Solving -5 + 6x = 19 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -5 + 6x + -3x = 19 + 3x + -3x Combine like terms: 6x + -3x = 3x -5 + 3x = 19 + 3x + -3x Combine like terms: 3x + -3x = 0 -5 + 3x = 19 + 0 -5 + 3x = 19 Add '5' to each side of the equation. -5 + 5 + 3x = 19 + 5 Combine like terms: -5 + 5 = 0 0 + 3x = 19 + 5 3x = 19 + 5 Combine like terms: 19 + 5 = 24 3x = 24 Divide each side by '3'. x = 8 Simplifying x = 8
| 4(y-6)=6(8+y) | | 3x-2y=63 | | (Y-3)+y=90 | | (x+7)(x-1)=(x+1)*2 | | 1/2y-1/3y | | 7/5x=-4 | | 15-x/2=x/5 | | 1/2y-1/3 | | 8x=40x+2 | | 5w=(4w+7)-(3w+1) | | 1/2(3z-5)+3(2z+4)=7 | | 8w-2w=1+17 | | 2x^2-4x-4=x-1 | | 2(y-3)=70 | | 12-3(2x+1)=7x-3(x+7) | | 11-7m=-52 | | 44-[4+8y-2(y+2)]=-4(3y-7)-[9(y-1)-12+20] | | -11+x-5-3=7x-7 | | 3+4x=-37 | | d+3/4=2 | | -14x=8 | | d+3/4=4 | | 4d+3/4=4 | | 27=70n | | g=-8-7 | | 3x^2-9x-120=0 | | -5+9+6= | | 4b-8-b=10b | | (2x-5)(3x+2)= | | 12x+6=-6 | | 4x+4=x+3 | | z-m=z+bz |